Il "Vindex sanguinis" di Isaac Viva (Amsterdam 1681): di una polemica sull'accusa di omicidio rituale - Facchini, Cristiana (Annali di storia dell'esegesi, 1999)
The essay analyzes a short treatise attributed to a Padua rabbi called Isaac Chaiim Cantarini, of the second half of the seventeenth century. It is perhaps one of the first Judaic works aiming to reject the charge of ritual murder levelled at the Jews. Through use of the scriptures, and Maimonides, the author shows how absurd the allegation of the existence of the crime, or even echoes of it, really is. He also raises other issues, not the least important being an invitation to intellectuals to utilize (as historical sources) documents emanating from public authorities, with the idea of improving our ability to evaluate particular phenomena. Finally, in a work which demonstrates a varied knowledge of both classical and ancient and modem Christian sources, he praises the tolerance of the Venetian Republic, and reveals a lively, cultured Jewish world, ready to defend itself from an accusation that often threatened the political status of European Jewish communities.